GMI, a fungal immunomodulatory protein from Ganoderma microsporum, induce apoptosis via β‐catenin suppression in lung cancer cells - Hsin, I‐Lun; Hsu, Jen‐Chieh; Wu, Wen‐Jun; Lu, Hsueh‐Ju; Wu, Ming‐Fang; Ko, Jiunn‐Liang (Environmental toxicology, 2018)
β‐catenin is important in development of lung cancer. In our previous study, GMI, a fungal immunomodulatory protein, inhibits lung cancer cell survival. The aim of this study is to evaluate the effect of GMI on β‐catenin inhibition and apoptosis induction. GMI induced apoptosis in lung cancer cells bearing wild‐type and mutated EGFR. GMI did not reduce the β‐catenin mRNA expression but suppressed the protein expressions of β‐catenin that resulted in the transcriptional downregulation of its target genes: survivin and cyclin‐D1. The transcriptional activation activity of β‐catenin was demonstrated by TOPFLASH/FOPFLASH luciferase reporter assay. Inhibition of GSK‐3β and proteasome blocked the inhibiting effect of GMI on β‐catenin and its target genes. β‐catenin silencing increased activation of apoptosis in GMI‐treated H1355 cells. This is the first study to reveal the novel function of GMI in inducing apoptosis via β‐catenin inhibition. These results provide a new potential of GMI in against lung cancer.